Study guide for Brunner & Suddarth's textbook of medical-surgical nursing - Moore, Leigh W. (Philadelphia, Pennsylvania : Wolters Kluwer, 2018)
Assess your understanding, apply what you've learned, and practice for success. Review what you're learned and test your understanding of the medical-surgical concepts presented in Brunner & Suddarth's Textbook of Medical-Surgical Nursing, 14th edition.
Basic concepts in nursing -- Biophysical and psychosocial concepts in nursing practice -- Concepts and challenges in patient management -- Perioperative concepts and nursing management -- Gas exchange and respiratory function -- Cardiovascular and circulatory function -- Hematologic function -- Immunologic function -- Musculoskeletal function -- Digestive and gastrointestinal function -- Metabolic and endocrine function -- Kidney and urinary function -- Reproductive function -- Integumentary function -- Sensory function -- Neurologic function -- Acute community-based challenges.
Keywords: NURSING -- PROBLEMS, EXERCISES, ETC